‘Shared efforts, brighter smiles’: a protocol for a randomised controlled study on the effectiveness of a parent-child orofacial myofunctional therapy programme post-adenoidectomy - Meng Zhao; Jianhua Liu; Jianchun Zhao; Aimin Wang; Haowei Du; Zhaoxia Wei (BMJ Open)
Introduction Adenoid hypertrophy has a high prevalence in children, often causing early orofacial muscle dysfunction that worsens facial deformities over time. While adenoidectomy (AT) alleviates airway obstruction, it only partially addresses the condition, leaving persistent neuromuscular habits. Orofacial myofunctional therapy is necessary for post-AT recovery but faces challenges such as poor adherence and ineffective parent-child communication. Dyadic interventions, which actively involve both parents and children, have shown advantages in improving treatment adherence and enhancing orofacial muscle function. Evidence suggests that dyadic intervention addresses both the child’s recovery needs and the caregiving capacity of parents, offering a more comprehensive solution for long-term intervention. Therefore, our team developed a parent-child dyadic orofacial myofunctional therapy (PCD-OMT) programme, offering insights into its potential application in paediatric healthcare to support comprehensive family-centred care.Method and analysis This two-arm, parallel-design, randomised controlled trial will recruit 80 dyads whose children performed AT from two hospitals in Qingdao, China. Dyads will be randomly allocated to two arms. Dyads randomly assigned to the intervention group will receive the PCD-OMT programme. Dyads randomly assigned to the control group will receive regular care. The primary outcomes are orofacial myofunction in children and parental care abilities. The secondary outcomes are children’s engagement and parental functioning. A feasibility and acceptability process will be employed to evaluate the viability in clinical practice. Outcomes will be collected at three checkpoints: baseline (T0), postintervention (T1) and after a 12-week follow-up phase (T2).Ethics and dissemination This study was approved by the Ethics Committee of Medical College of Qingdao University (QDU-HEC-2023216). The results will be published in peer-reviewed publications and presented in international conferences.Trial registration number ChiCTR2400091466.